A Comprehensive esthetic Management of Fluorosed teeth with use of Microabrasion, In-office Bleaching and Resin Infiltration: A case report - Kanwalpreet Kaur Bhullar; Smiley Goyal; Rupam Kaur Virk; Harkiran Sahiwal (Journal of Oral Research and Review)
Enamel hypomineralization is a condition that affects the quality of enamel, resulting in a change in its translucency and color. Increasingly, patients are asking for these imperfections to be treated and it is now possible to intervene with minimally invasive methods to restore the aesthetics of these dental elements. In this case report, we report the case of a 23-year-old patient suffering from fluorosis and treated with microabrasion, in-office bleaching followed by resin infiltration. The treatment satisfied the patient and the clinicians.